1995
DOI: 10.1111/j.1365-2125.1995.tb04441.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive medication use, sensori‐motor function and falls in older women.

Abstract: and number of medical conditions. Use of any two psychoactive medications was also significantly associated with falling frequency (Chi-square = 13.91, df = 1, P < 0.01). 4 Path analysis revealed a significant direct association (P < 0.001) between psychoactive medication use and falls, and a significant indirect association mediated via reduced physiological functioning (P < 0.001). Postural hypotension was not significantly associated with falls (RR = 1.37, 95% CI = 0.84-2.22). 5 The findings suggest that ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 23 publications
2
46
0
1
Order By: Relevance
“…In our study, however, despite significantly reducing the proportion of residents with postural hypotension, there was no corresponding reduction in falls, suggesting that postural hypotension alone is not a key risk factor for falls in this population. A study of psychoactive medication use and falls in elderly people also reported a lack of association between postural hypotension and falls [15]. Our project is one of the few trials that have attempted to examine the effectiveness of a fall prevention approach amongst those in institutional care [16].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, however, despite significantly reducing the proportion of residents with postural hypotension, there was no corresponding reduction in falls, suggesting that postural hypotension alone is not a key risk factor for falls in this population. A study of psychoactive medication use and falls in elderly people also reported a lack of association between postural hypotension and falls [15]. Our project is one of the few trials that have attempted to examine the effectiveness of a fall prevention approach amongst those in institutional care [16].…”
Section: Discussionmentioning
confidence: 99%
“…25 However, prospective studies examining this relationship are small, of short duration, and inconsistent with some showing OH to be associated with risk of falls [26][27][28][29][30] and others showing no association. [31][32][33][34][35][36][37][38] One of the larger prospective studies, conducted in 844 nursing home residents, reported that OH was associated with a higher risk of falls (relative risk: 2.1, 95% CI: 1.4, 3.1) during 1.2 years of follow-up. 26 In contrast, a larger prospective study of 1,517 ambulatory Chinese patients, showed that OH was not associated with falls after adjustment for other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…At the very least, adults identified as having OH should receive special consideration when prescribed medications known to worsen alertness, affect balance, or increase the risk of falls. 34,37,39 Moreover, interventions useful in preventing falls may be worth implementing in adults with OH such as physical therapy. 46 This study has a number of important limitations.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Although there are limited interventions available to modify these endogenous fall risk factors, modifiable exogenous factors may also contribute to fall risk in MS. In older people, in whom fall risk is most well understood, the use of multiple medications, 12 particularly psychotropics, has been found to significantly increase fall risk, 13,14 and modifying medication prescription can prevent falls. 15,16 Many patients with MS are prescribed and take multiple medications, including many neurologically active drugs.…”
mentioning
confidence: 99%